2009 International Conference on Future Computer and Communication 2009
DOI: 10.1109/icfcc.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Camera Calibration Using MultiLayer Perceptron Type Neural Network

Abstract: This paper presents a 3D camera calibration method based on a nonlinear modeling function of an artificial neural network. The neural network employed in this paper is primarily used as a nonlinear mapper between 2D image points and points of a certain space in 3D real world. The neural network model implicitly contains all the physical parameters, some of which are very difficult to be estimated in the conventional calibration methods. MutiLayer Perceptron Type Neural Network (MLPNN) is employed to implement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Thus, we cannot train the network using any supervised learning technique such as a gradient descent algorithm. In [13], it is shown that a network can be trained if the z coordinate is set to a constant value. However, the network then can be applied only to some limited cases where the distance between a camera and target points is constant.…”
Section: B Neural Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we cannot train the network using any supervised learning technique such as a gradient descent algorithm. In [13], it is shown that a network can be trained if the z coordinate is set to a constant value. However, the network then can be applied only to some limited cases where the distance between a camera and target points is constant.…”
Section: B Neural Learningmentioning
confidence: 99%
“…Although there are many camera models available, pinhole camera model is the most widely used mainly due to its simplicity [2,7,13,16].…”
Section: Camera Matrix Of Perspective Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…A solution to correct the geometrical distortion in image is typically used mathematical algorithm of polynomial equations to estimate and interpolate coordination of image [2][3][4][5]. An artificial neural network (ANN) is widely applied to solve various engineering problems such as pattern recognition, optimization and modeling [6,7] and also in computer vision [8,9]. The ANN is suitable to be employed for solving the problems that require complex models.…”
Section: Introductionmentioning
confidence: 99%